1996
DOI: 10.1111/j.1570-7458.1996.tb00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GNA and other mannose binding lectins on development and fecundity of the peach‐potato aphid Myzus persicae

Abstract: Three mannose‐binding lectins were assayed in artificial diets for their toxic and growth‐inhibitory effects on nymphal development of the peach‐potato aphid Myzus persicae. The snowdrop (Galanthus nivalis) lectin GNA was the most toxic, with an induced nymphal mortality of 42% at 1500 μg ml−1 (30 μM) and an IC50 (50% growth inhibition) of 630 μg ml−1 (13 μM). The daffodil (Narcissus pseudonarcissus) lectin NPA and a garlic (Allium sativum) lectin ASA induced no significant mortality in the range 10–1500 μg ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 34 publications
(39 reference statements)
9
80
0
Order By: Relevance
“…After feeding GNA to the insects at doses between 0.01 and 0.1% (w/v), the presence of the lectin in the honeydew of GNA-fed insects was demonstrated. This agrees with Sauvion et al (1996) who indicated that neonates of the green peach aphid (Myzus persicae) fed with an artificial diet containing GNA, Narcissus pseudonarcissus lectin (NPA), Allium sativum agglutinin (ASA, garlic), or Concanavalin A (ConA, jack-bean Canavalia ensiformis), showed increased mortality and a negative effect on weight gain. Interestingly, at a low concentration (0.001%), GNA enhanced the growth of nymphs, which might be attributed to a probiotic effect of lectins at low concentrations, as seen in mammals (Banwell et al, 1993).…”
Section: Gna: a Mannose-specific Lectin With Negative Effects On Sevesupporting
confidence: 79%
See 2 more Smart Citations
“…After feeding GNA to the insects at doses between 0.01 and 0.1% (w/v), the presence of the lectin in the honeydew of GNA-fed insects was demonstrated. This agrees with Sauvion et al (1996) who indicated that neonates of the green peach aphid (Myzus persicae) fed with an artificial diet containing GNA, Narcissus pseudonarcissus lectin (NPA), Allium sativum agglutinin (ASA, garlic), or Concanavalin A (ConA, jack-bean Canavalia ensiformis), showed increased mortality and a negative effect on weight gain. Interestingly, at a low concentration (0.001%), GNA enhanced the growth of nymphs, which might be attributed to a probiotic effect of lectins at low concentrations, as seen in mammals (Banwell et al, 1993).…”
Section: Gna: a Mannose-specific Lectin With Negative Effects On Sevesupporting
confidence: 79%
“…Increased mortality and negative effects on growth and development were also noted in other species, both lepidopteran and hemipteran (Fitches et al, 2001;Gatehouse et al, 1999;Sauvion et al, 1996). The N-acetylglucosamine-specific GSII lectin from Griffonia simplicifolia showed insecticidal properties against the cowpea weevil (Callosobruchus maculatus) (Zhu et al, 2006).…”
Section: Other Constitutively Expressed Lectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The snowdrop lectin, GNA, is toxic to brown planthopper (Nilaparvata lugens; Powell et al, 1998;Tang et al, 2001) and tomato moth (Lacanobia oleracea) larvae (Fitches et al, 1997;Gatehouse et al, 1997Gatehouse et al, , 1999 as well as to several aphid species (Hilder et al, 1995;Rahbé et al, 1995;Gatehouse et al, 1996;Sauvion et al, 1996). Concanavalin A (lectin from Canavalia ensiformis) shows significant antimetabolic activity toward third-instar nymphs of taro planthopper (Tarophagous proserpina; Powell, 2001).…”
mentioning
confidence: 99%
“…Studies such as pyramided rice lines (Foissac et al, 2000;Nagadhara et al, 2003); marker genefree transgenic tobacco (Bharathi et al, 2011); chickpea (Chakraborti et al, 2009); rice (Yarasi et al, 2008) show effectiveness of lectins against sucking insect population. The efficacy of snowdrop (G. nivalis) and garlic lectins have been studied against phloem feeding Aphis craccivora, cotton aphids A. gossypii (Sauvion et al, 1996), red spider mite of tea (Roy et al, 2008), cotton leafworm and sapsucking planthoppers (Powell, 2001). Lectin genes, as compared to the Bt genes are produced in storage parts of the plant as bulbs and in very minute amounts in roots and leaves.…”
Section: Discussionmentioning
confidence: 99%